Sistem Pengarsipan Digital pada Dinas Kelautan Provinsi NTT - Jefri uly binu; Max ABR Soleman Lenggu; Yohanes Payong (Universitas Kristen Immanuel, 2023)
The Digital Archiving System at the Marine Service of East Nusa Tenggara Province in archiving incoming mail, outgoing mail active and inactive archives is still manual by being recorded in the agenda book which makes it difficult to find files. It aims to create a filing system for incoming mail, outgoing mail, active archives and inactive archives to facilitate archiving and searching. The research method used is the method of interview, observation, literature study and internet browsing, while for application development the method used is the Waterfall method. The software used is windows 10, Visual Studio code, Xampp Control Panel v3.2.2 PHP, mysql. The results of the application that are built are expected to help the Department and also for website visitors. Keywords: Archiving system, incoming mail, outgoing mail, PHP active and inactive archives, mysql